Imaging of brain oxygenation with magnetic resonance imaging: A validation with positron emission tomography in the healthy and tumoural brain. Issue 7 (July 2017) - Valable, Samuel; Corroyer-Dulmont, Aurélien; Chakhoyan, Ararat; Durand, Lucile; Toutain, Jérôme; Divoux, Didier; Barré, Louisa; MacKenzie, Eric T; Petit, Edwige; Bernaudin, Myriam; Touzani, Omar; Barbier, Emmanuel L
The partial pressure in oxygen remains challenging to map in the brain. Two main strategies exist to obtain surrogate measures of tissue oxygenation: the tissue saturation studied by magnetic resonance imaging (St O2 -MRI) and the identification of hypoxia by a positron emission tomography (PET) biomarker with 3-[ 18 F]fluoro-1-(2-nitro-1-imidazolyl)-2-propanol ([ 18 F]-FMISO) as the leading radiopharmaceutical. Nonetheless, a formal validation of St O2 -MRI against FMISO-PET has not been performed. The objective of our studies was to compare the two approaches in (a) the normal rat brain when the rats were submitted to hypoxemia; (b) animals implanted with four tumour types differentiated by their oxygenation. Rats were submitted to normoxic and hypoxemic conditions. For the brain tumour experiments, U87-MG, U251-MG, 9L and C6 glioma cells were orthotopically inoculated in rats. For both experiments, St O2 -MRI and [ 18 F]-FMISO PET were performed sequentially. Under hypoxemia conditions, St O2 -MRI revealed a decrease in oxygen saturation in the brain. Nonetheless, [ 18 F]-FMISO PET, pimonidazole immunohistochemistry and molecular biology were insensitive to hypoxia. Within the context of tumours, St O2 -MRI was able to detect hypoxia in the hypoxic models, mimicking [ 18 F]-FMISO PET with high sensitivity/specificity. Altogether, our data clearly support that, in brain pathologies, St O2 -MRI could be a robust and specific imaging biomarker to assess hypoxia.